Sox10 Mediates Luminal Lineage Identity and Tumor-Initiating Capacity in HER2/Neu-Driven Mammary Tumorigenesis - Garland, Brennan (Université d'Ottawa / University of Ottawa, 2026)
The SRY-HMG-Box transcription factor SOX10 plays a critical role in neural crest development. While it has recently been identified as a mediator of the mammary stem/progenitor state, as well as a marker for aggressive basal-like breast cancer, its precise function in epithelial tumorigenesis remains unclear. Here, we identify Sox10 as a key regulator of tumor-initiating activity in HER2/Neu-driven mammary cancers. Genetic ablation of Sox10 in the luminal compartment of mice resulted in delayed but normal mammary gland development. In a murine model of HER2-positive breast cancer, Sox10 deletion conferred a dose-dependent delay in tumor onset, with a complete loss of tumor initiation in Sox10-deficient luminal cells. CRISPR/Cas9-mediated Sox10 inactivation in HER2/Neu-transformed tumor cells led to reduced 3D invasion and diminished self-renewal in mammosphere assays. Established Sox10-deficient cell lines exhibited markedly impaired growth in orthotopic transplant models and failed to colonize lung tissue following tail vein injection, suggesting a loss of tumor-initiating capacity. Transcriptomic profiling revealed that Sox10-deficiency in HER2/Neu-transformed tumor cells leads to erosion of luminal cell identity and acquisition of basal/stem-like markers. Collectively, these findings demonstrate that Sox10 is required for a permissive cell progenitor state for HER2/Neu-driven tumor initiation and is critical to sustain the invasive and self-renewing traits that drive tumor progression and metastasis. The findings provide a novel therapeutic approach in the targeting of Sox10 signalling programs in the mammary epithelium which seemingly give rise to tumor cells of origin in HER2⁺ breast cancers.
Keywords: Cancer Stem Cells; Molecular Biology; Sox10